Beyond the Chrononormativity of the Bildungsroman: queer temporalities in "Bad Habit" (2023), by Alana S. Portero - Castillo Bel, Laura (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This paper proposes an analysis of Alana S. Portero's recent work, Bad Habit (2023), which narrates the journey from childhood to adolescence of a trans woman in Madrid in the eighties and nineties. Bildungsromane of the cisheteronormative domain have tended to perpetuate the classical patterns of the literary genre’s tradition, creating the false impression that there is only one narrative of childhood and adolescence representative of all human beings. However, Portero's novel dismantles this homogenizing approach, by proposing a vital growth, which does not consist of a mere sum of experiences and coherent decisions that lead successively and linearly towards the formation of a single and immutable identity; but rather it coexists with comings and goings, which form an identity crucible in which past and present are conceived as a mosaic and not so much as an evolution.  With the aim of dismantling this hegemonic Bildungsroman tradition, it is proposed to analyze Bad Habit from the theoretical approaches of queer temporality (Dinshaw et al., 2007; Freeman, 2010; Halberstam, 2005; Love, 2007), which can elucidate the differences around the experience of time, body, family or identity, with which the queer experience enriches this specific literary genre.
Keywords: Alana S. Portero; Queer Temporalities; Bildungsroman; Bad Habit; Chrononormativity